Calcaneal quantitative ultrasound analysis in Korean and Japanese elite female athletes - Song, H.-S.; Min, S.-K.; Ishigami, H.; Lee, K.; Rozikin, H.; Nakazato, K. (International Journal of Applied Sports Sciences, 2017)
The relationships between bone properties and cumulative mechanical impact were examined in elite female athletes (N=70) and age, gender matched non-athlete controls (N=64). The athletes were divided into 3 groups, namely, high-impact (HI: body weight bearing with high mechanical loading, N=18), medium-impact (MI: body weight bearing with medium load, N=36), and low-impact (LI: body weight bearing with low load, N=16). Effects of mechanical impact on quantitative ultrasonography (QUS) parameters, including speed of sound (SOS), broadband ultrasound attenuation (BUA), and stiffness index (SI), were assessed using a multiple linear regression model adjusted for age, body weight, height, body mass index, and impact. We found that BUA was positively influenced by MI (P < 0.05). SOS was negatively influenced by LI (P < 0.05). SI was positively influenced by MI (P < 0.05). In conclusion, the bone qualities in elite female athletes differ depending on their cumulative impacts